15. Persepsi Bersama Indonesia-Australia dalam Hibah Dana dan Peralatan Investigasi Cyber Crime dari Australia Kepada Indonesia - Supriyadi, Bambang; Susiatiningsih, Hermini; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The history of the relations between Indonesia and Australia highlighted by several eventsthat create relations of two countries became heaving and worries some people in Australiawho considers Indonesia as one of the threats to the security of Australia. But these twothings does not impede Indonesia and Australia to conduct a number of cooperation andother collective efforts to overcome the various threats to the security of both countries,one of which is the threat of cyber crime. This research aimed to analyze factors that affectpolicies taken by Australia in providing financing and equipment of cyber crimeinvestigation to Indonesia. This research uses the concept of collective identity from theconstructivist theory that driven by perceptions of a threat in explaining the behavior of astate. The results of this research indicate that the perception of the two countries in viewof the threat of cyber crime made the two countries have a collective identity as the twocountries that tried to combat cyber crime.